The effects of E-Commerce drivers on export market strategy: fundamental study on the perception of Small and Medium Enterprises (SME's) in Labuan - Caroline Rosie Jeffrey Nasah; Ang, Magdalene Chooi Hwa; Minah Japang; Goh, Say Leng (Universiti Malaysia Sabah, 2009)
The advancement of e-commerce technologies and the rapid global expansion of firms have been the major trends in today's modem business landscape. The e-commerce technologies have led to entirely new possibilities for exporters to access new markets and improve their efficiency in terms of receiving customer orders and handling inquiries (Bennett 1997; Hamill 1997; Prasad, Ramamurthy, and Naidu 2001; Samiee 1998). The globalization of the world markets therefore has led to explosive growth of global trade and exporting firms around the world.